2001
DOI: 10.1155/s1110724301000146
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Rat Peripheral Blood Lymphocytes by the Anticancer Drug CI‐994 (Acetyldinaline)

Abstract: CI-994 (acetyldinaline) is an investigational anticancer drug currently in clinical trials. In preclinical safety studies in rats and dogs, CI-994 resulted in significant toxicity to bone marrow and lymphoid tissue. To determine if apoptosis was involved in CI-994 toxicity, peripheral blood lymphocytes were isolated from untreated male Wistar rats and exposed to CI-994 (1, 3, 10, or 30 μM) in vitro for up to 24 hours. Morphological and biochemical features of apoptosis were evaluated using several techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…58 However, studies have demonstrated that among other actions, it possesses histone deacetylation activity. 59 Following CI-994 administration, inhibition of both histone deacetylation and cellular proliferation at the G 1 to S transition phase of the cell cycle occur. 58 Recently, Phase I studies have concluded and the recommended Phase 2 doses established.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…58 However, studies have demonstrated that among other actions, it possesses histone deacetylation activity. 59 Following CI-994 administration, inhibition of both histone deacetylation and cellular proliferation at the G 1 to S transition phase of the cell cycle occur. 58 Recently, Phase I studies have concluded and the recommended Phase 2 doses established.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%
“…The LDH assay measures the content of LDH released from cells due to damage to cell membranes as a result of necrosis and/or late apoptotic processes [43,44]. LDH cell viability experiments demonstrated that cell viability in MCF-7- and MCF-12A cells decreased to 83.5% and 92.4% respectively compared to controls ( P < 0.05) after 24 h treatment with C9+DCA (C9 = 130 nM and DCA = 7.5 mM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, reaction with 0.05% of 3-3′-diaminobenzidine tetrahydrochloride (DAB) was monitored under the microscope (Graziano, Spoon, Cockrell, Rowse, & Gonzales, 2001). An optimal signal-to-background ratio was obtained at 1:4 dilution of the antibody.…”
Section: Apoptosis Assaymentioning
confidence: 99%
“…An optimal signal-to-background ratio was obtained at 1:4 dilution of the antibody. Then, reaction with 0.05% of 3-3′-diaminobenzidine tetrahydrochloride (DAB) was monitored under the microscope (Graziano, Spoon, Cockrell, Rowse, & Gonzales, 2001).…”
Section: Apoptosis Assaymentioning
confidence: 99%